Plastic to fuel : effect of catalyst support for nickel catalst - Fa, Fu Win (2016)
The depletion of fossil fuel encourages development of alternative energy resources. Investigation on converting waste to fuel via pyrolysis including plastic waste; one of major waste composition, is recently explored by many researchers. One of the goal of the current researches is to develop a lower cost of catalyst. However, low yield and fuel quality are among major obstacles to scale up this process. The aim of this research is to synthesis, test and characterize nickel catalyst at various supports for plastic to fuel via catalytic pyrolysis. High Density Polyethylene (HDPE) resin was characterized by using Thermogravimetric Analyser (TGA). A 20 wt% of nickel catalyst with either alumina or oil palm ash support was synthesized via wet impregnation. High Density Polyethylene (HDPE) resin was used at a plastic to catalyst weight ratio of 10:1. The catalyst was tested in a batch one litre borosilicate reactor that heated up to 450 C for half an hour. A condenser was used to liquefy the product. Solid, liquid and gas product was obtained. Catalyst pore structure, catalyst surface morphology and composition was determined to characterize the catalyst by using Brunauer, Emmett and Teller (BET) and Scanning electron microscope (SEM) respectively. The uncondensed gas was collected in gas bag. The gas product was analysed by using Gas Chromatography-Thermal Conductivity Detector (GC-TCD). The calorific value, viscosity, clarity and yield of the liquid products was also determined. Gas chromatography-mass spectrometry (GC-MS) was used to determine the liquid fuel composition. The use of ash as a catalyst support for nickel in pyrolysis process has achieved a high liquid product yield of 75.32 wt% and an equivalent quality to that of commercial fuel. Besides, a gas product that rich in hydrogen (66.83 mol%) and methane gas (4.92 mol%) was obtained. Finding from this work is vital for generating cheap catalyst for plastic waste pyrolysis process. In conclusion, cheap and green technology for alternative fuel production via plastic pyrolysis using ash as catalyst support can be commercialized and scale up.